Efficiency droop and carrier transport in AlGaN epilayers and heterostructures. Issue 5 (30th January 2015) - Mickevičius, J.; Tamulaitis, G.; Jurkevičius, J.; Shur, M. S.; Shatalov, M.; Yang, J.; Gaska, R.
<x xml:space="preserve">Abstract</x> The photoluminescence (PL) spectroscopy of AlGaN epilayers and heterostructures under quasi‐steady‐state conditions at different excitations in a wide temperature range from 8 to 300 K established the connection between the internal quantum efficiency, efficiency droop, and carrier localization. The carrier localization conditions were estimated from the temperature dependences of the PL band peak positions. The temperature dependences of the PL intensity were fitted using the Arrhenius‐type equation with two activation energies, which were attributed to the carrier redistribution within the localized states and carrier delocalization, respectively. The delocalization of the localized carriers affects the luminescence efficiency via the enhancement of the two mechanisms of opposite signs: the bimolecular radiative recombination and nonradiative recombination due to an increased probability to reach nonradiative recombination centers.